Use of NIRS to explore skeletal muscle oxygenation during different training sessions in professional boxing - Usher, A.; Babraj, J. (European Journal of Applied Physiology, 2024)
Purpose The physiological examination of boxing has been limited to systemic response in amateur athletes. The demands of professional boxing have been overlooked, despite the different competition format. We sought to determine the physiological demands placed on skeletal muscle in professional boxing.